Effect of a leukotriene inhibitor (MK886) on nitric oxide and hydrogen peroxide production by macrophages of acutely and chronically stressed mice - Sforcin, Jose Mauricio; Nunes, Gladston A.; Missima, Fabiane; Sa-Nunes, Anderson; Faccioli, Lucia H. (Pharmaceutical Press-royal Pharmaceutical Soc Great Britian, 2007)
We evaluated the effect of a leukotriene inhibitor (MK886) on nitric oxide (NO) and hydrogen peroxide (H2O2) production by peritoneal macrophages of mice subjected to acute and chronic stress. Acute stress was induced by keeping mice immobilized in a tube for 2 h. Chronic stress was induced over a 7-day period by the same method, but with increasing duration of immobilization. The effects of MK886 were investigated in-vitro after incubation with peritoneal macrophages, and in-vivo by submitting mice to stress and treating them daily with MK886. Supernatants of macrophage cultures were collected for NO determination and adherent cells were used for H2O2 determination. Macrophages from mice submitted to acute or chronic stress showed no alterations in H2O2 production. However, macrophages of acutely and chronically stressed mice showed inhibition of NO after incubation with MK886 in-vitro. Administration of MK886 to chronically stressed mice increased generation of H2O2 and inhibited production of NO. Our data suggest an important role of leukotrienes in NO synthesis, which is important in controlling replication of several infectious agents, mainly in stressed and immunosuppressed animals.